Channel-based determinants and phase-focused traits in the adoption process of a sustainable development strategy for the hog industry in Canada. Issue 11 (2nd November 2015) - Charlebois, Sylvain; Griffith, ChristopherJ.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The current study examines the use of sustainability as strategic cornerstone for a marketing channel in a mature market, particularly in the hog industry in the Canadian Province of Quebec. Due to the growing attention to sustainability, and the international trend towards agricultural trades and stakeholder involvement in food, there is a need for a system-based approach in the field of food systems sustainability. Design/methodology/approach Twelve (12) semi-structured individual interviews were conducted amongst marketing managers working for different organizations within the Quebec hog marketing channel. The organizations chosen vary depending on the size, level of integration, and involvement in the industry, to create a sample that adequately represents the industry. For the purpose of this research, three (3) primary producers, one (1) veterinarian, three (3) licenced abattoirs, one (1) food processor, one (1) distributor, one (1) independent retailer and two (2) types of food service facility, one from a franchise system and the other from a high-end restaurant were questioned regarding the current state of the industry, as well as the impact of sustainable development on their strategic plans. Findings The Canadian hog and pork industry is currently facing strong competition from several fronts: the United States and South America, a population with increasingly sophisticated demands, a strong Canadian dollar and a significant increase in input costs, particularly in respect to oil and corn. To be able to meet this competition, and in order to prosper in an uncertain marketplace, marketing channel believes that it must reduce its production costs, increase product awareness in the domestic market and promote cooperation among industry members. Research limitations/implications This research is mainly concerned with the Quebec hog industry. External validity has not been achieved with the current research. In addition, a lack of distributor availability to answer the interview questions limits researchers' capacity to extrapolate results to all retailers. Meetings with other food distributors would be required to verify the accuracy of results. Although this study is exploratory in nature, several appealing research avenues emerge. First, the research focuses primarily on members of the distribution network, but does not consider the consumers' point of view. It would be fruitful to study the impact of sustainable development on the perceived product quality by measuring consumers' intent to purchase. Practical implications The principal point of interest that makes this case worthy of study and of potential application to future business modeling is how sustainability and sustainable development is perceived throughout various marketing channels. The Quebec hog industry faces strong competition from several countries that are able to offer a similar product at a lower cost. The mature market consists of a limited number of producers interested in offering a product on the market at the lowest possible price. Originality/value To our knowledge, no study has been conducted to evaluate the use of sustainability as strategic cornerstone for a marketing channel in a mature market, particularly in the hog industry. Many studies have been conducted in a context of emerging markers. However, very few studies addressed the issue in an established economic environment.